A kora keresztény mártíromság kérdései Boudewijn Dehandschutter kutatásainak tükrében - D. Tóth, Judit (Studia Litteraria, 2012)
The review makes an attempt to summarize the most important questions of the research on ancient Christian martyrdom, relying on the writings of professor Boudewijn Dehandschutter (Leuven), the internationally acknowledged scholar who died recently and in honour of whom a Festschrift has been published. Dehandschutter’s research focussed on Martyrium Polycarpi, a text dating back to the second century AD, which almost paradigmatically shows the most important questions of ancient Christian martyrdom, the nature of its cult and origins. The review touches upon the following questions: philology, etymology, theology, poetics and genre, various phenomena connected to the history of ideas and the cults regarding the cult of the martyrs from the beginnings to the end of the forth century AD.